Epigenetic Clock Deceleration and Maternal Reproductive Efforts: Associations With Increasing Gray Matter Volume of the Precuneus - Nishitani, Shota; Kasaba, Ryoko; Hiraoka, Daiki; Shimada, Koji; Fujisawa, Takashi X.; Okazawa, Hidehiko; Tomoda, Akemi (Frontiers in Genetics, 2022)
Reproductive efforts, such as pregnancy, delivery, and interaction with children, make maternal brains optimized for child-rearing. However, extensive studies in non-human species revealed a tradeoff between reproductive effort and life expectancy. In humans, large demographic studies have shown that this is the case for the most part; however, molecular marker studies regarding aging remain controversial. There are no studies simultaneously evaluating the relationship between reproductive effort, aging, and brain structures. We therefore examined the associations between reproductive efforts (parity status, number of deliveries, motherhood period, and cumulative motherhood period), DNA methylation age (mAge) acceleration (based on Horvath’s multi-tissue clock and the skin & blood clock), and the regional gray matter volumes (obtained through brain magnetic resonance imaging (MRI) using voxel-based morphometry) in 51 mothers aged 27–46 years of children in early childhood. We found that increasing reproductive efforts were significantly associated with decelerated aging in mothers with 1–4 children, even after adjusting for the confounding effects in the multiple linear regression models. We also found that the left precuneus gray matter volume was larger as deceleration of aging occurred; increasing left precuneus gray matter volume, on the other hand, mediates the relationship between parity status and mAge deceleration. Our findings suggest that mothers of children in early childhood, who have had less than four children, may benefit from deceleration of aging mediated via structural changes in the precuneus.